2014
DOI: 10.1175/bams-d-12-00241.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Climate Prediction: An Update from the Trenches

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
470
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 494 publications
(499 citation statements)
references
References 140 publications
12
470
1
Order By: Relevance
“…We will also identify major science issues and challenges for understanding and extracting the imprints of internal climate modes in observed sea level change patterns, with a hope of contributing to decadal sea level predictions, which emerge as pressing priorities in climate research today (e.g., Goddard et al 2009;Hurrell et al 2009;Meehl et al 2009Meehl et al , 2014Pohlmann et al 2009;Doblas-Reyes et al 2011;Polkova et al 2015). In Sects.…”
Section: Introductionmentioning
confidence: 99%
“…We will also identify major science issues and challenges for understanding and extracting the imprints of internal climate modes in observed sea level change patterns, with a hope of contributing to decadal sea level predictions, which emerge as pressing priorities in climate research today (e.g., Goddard et al 2009;Hurrell et al 2009;Meehl et al 2009Meehl et al , 2014Pohlmann et al 2009;Doblas-Reyes et al 2011;Polkova et al 2015). In Sects.…”
Section: Introductionmentioning
confidence: 99%
“…The data are downloaded from the Earth System Grid Federation (ESGF) at the address https ://esgf-data.dkrz.de/proje cts/esgf-dkrz/. Information about the 11 models are summarized in Tables 1 and 2, and more details can be found in (Meehl et al 2014). …”
Section: Cmip5 Decadal Hindcast Simulationsmentioning
confidence: 99%
“…However, due to the lack of perfect initial conditions and the inability to perfectly model the climate system, there are unavoidable uncertainty and inadequacy in the model simulations (Palmer 2000;Slingo and Palmer 2011), and even the internal variability is so far not fully captured by current models (Doblas-Reyes et al 2013;Meehl et al 2014). In this situation, are current models able to reproduce the LTM that was detected from observational data, and further capture the memory part M(t)?…”
Section: Introductionmentioning
confidence: 99%
“…It is calculated here as the difference between the mean SST anomalies in the North Atlantic and the global mean SST anomalies between 60 • S and 60 • N following the definition of Trenberth and Shea (2006). Previous studies have shown that the predictive skill for AMO can be improved by initialisation (Meehl et al 2014) The positive impact of the initialisation for the AMO index persists for the whole forecast time (Fig. 9).…”
Section: Impact On Some Modes Of Climate Variabilitymentioning
confidence: 99%